Teaching and Learning Proposition: The Use of 3D Ergonomic Board - Audu Omar Ahmed Otobo; Ijudai Musa Palnam (Progress in Language, Literature and Education Research Vol. 6, 2024)
The Nigerian instructional structure is experiencing a breakdown of the educational infrastructure, the poor salaries of educationists, the decline of a construing culture, the incessant strikes in the education system, the anti-intellectual attitudes of the past and present regimes or lack of job opportunities for the products of the system. The caprice for the study came from an indigenous-designed instructional board for teaching learners in nursery/primary schools (2 – 10 years) and the task whose overall topic is the reminiscence, and retention of visual aid use in the pedagogy. The study is to appraise the opinion of toddlers/teachers about the helpfulness of 3D visuals (ergonomic board); the clarity of the intended functions of the 3D-visuals in the toddler’s lessons instruction and support from the producers in using them; and why visuals (conventional visual aids) in schoolroom instruction are misjudged/misinterpreted; their view about the functions in specific (conventional visuals) for the instruction pedagogy; and other sources of visuals provided other than the lesson’s instruction. Four nursery/primary schools participated in the study. Seventy-two (72) toddlers/teachers participated in the study. The study examined using quantitative and qualitative approaches for statistical analysis (using pie-chart and histogram). The findings suggested that the aspects of visual items selected for comment and description are to some extent circumscribed by toddler learners’ linguistic resources. Understandably, the point made by researchers referred to that visuals often fail to support learning as effectively as they might because they are not regarded as a full-fledged information mode that requires the same careful processing as verbal text, is borne out by the findings. Recommendation, the accountability is above all on producers of kid’s instructional materials: authors, editors, designers, and illustrators of the materials. The implication of this is that toddlers’ instructional materials should, as in the case of illustrated books include both an overt explanation of the overall philosophy toward visuals and an overview of their use. 3D-visuals have, among many other “visual sustenance characteristics” the budding to aid teaching and learning by reducing cognitive load, providing mnemonic support, conceptualizing language input on various levels, clarifying learning procedures, visualizing grammatical structures, facilitating comprehension, stimulating lexical production and, if teachers rather than research psychologists are to be believed, motivate learners and make teaching and learning more pleasurable.